MODEL PEMBELAJARAN AKTIF COURSE REVIEW HORAY (CRH) UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA - Sri Hartati (Absis: Mathematics Education Journal, 2020)
The objective of this study is to improve students' learning outcome on mathematics through the active learning model of Course Review Horay (CRH) in class VII H students of the odd semester of SMP Negeri 2 Weru in the academic year 2019/2020. The subjects of this study are 32 students of class VII H. Data collection techniques are using documentation, observation, and written tests. Data collection tools are the form of observation sheets, test items, and a list of scores. Data analysis use comparative descriptive analysis followed by reflection. Each cycle consists of four steps, namely: (1) Planning, (2) Implementing Actions, (3) observing, and (4) Reflecting. The results show that there is an increase in students 'Mathematics learning achievement, the average score of students' mathematics learning achievement increase, namely before the action was 69.8, in cycle I is 72.9 and in cycle II is 82.9. In addition, the percentage of student learning completeness also increase, namely before the action was 53.1%, cycle I is 65.6% and cycle II is 93.8%. So it can be concluded that the CRH active learning model can improve students' learning outcome.